2022
DOI: 10.3390/cells11040713
|View full text |Cite
|
Sign up to set email alerts
|

S1P Signalling Axis Is Necessary for Adiponectin-Directed Regulation of Electrophysiological Properties and Oxidative Metabolism in C2C12 Myotubes

Abstract: Background: Adiponectin (Adn), released by adipocytes and other cell types such as skeletal muscle, has insulin-sensitizing and anti-inflammatory properties. Sphingosine 1-phosphate (S1P) is reported to act as effector of diverse biological actions of Adn in different tissues. S1P is a bioactive sphingolipid synthesized by the phosphorylation of sphingosine catalyzed by sphingosine kinase (SK) 1 and 2. Consolidated findings support the key role of S1P in the biology of skeletal muscle. Methods and Results: Her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 83 publications
(108 reference statements)
2
6
0
Order By: Relevance
“…SK1 and SK2, characterized by different tissue distribution and subcellular localization, can modulate fundamental cellular processes, such as apoptosis and proliferation, even in opposite ways [35]. Our findings support the concept that SK isoforms may have overlapping functions, as already reported for the pro-myogenic action exerted by IGF [36] and for the modulation of electrophysiological properties and oxidative metabolism by adiponectin in skeletal muscle [37]. Of note, SK1 and SK2 are equally required for the chemotactic effect exerted by epidermal growth factor (EGF) in breast cancer cells [38] and by TGFβ in esophageal cancer cells [39].…”
Section: Discussionsupporting
confidence: 87%
“…SK1 and SK2, characterized by different tissue distribution and subcellular localization, can modulate fundamental cellular processes, such as apoptosis and proliferation, even in opposite ways [35]. Our findings support the concept that SK isoforms may have overlapping functions, as already reported for the pro-myogenic action exerted by IGF [36] and for the modulation of electrophysiological properties and oxidative metabolism by adiponectin in skeletal muscle [37]. Of note, SK1 and SK2 are equally required for the chemotactic effect exerted by epidermal growth factor (EGF) in breast cancer cells [38] and by TGFβ in esophageal cancer cells [39].…”
Section: Discussionsupporting
confidence: 87%
“…This outcome is in agreement with previous observations on atrophic myotubes made by our research group. Indeed, atrophic myotubes showed an increased membrane permeability and a reduction of cell capacitance 16 . Here, we demonstrate that the presence of sodium pyruvate in CM CT26 counteracted the occurence of these alterations, showing membrane parameters similar to untreated myotubes.…”
Section: Discussionmentioning
confidence: 52%
“…When filled, the patch pipette's resistance was 1.5–2 MΩ. The patch pipette was inserted in a CV203BU head‐stage (Axon Instruments, Foster City, CA) attached to a three‐way coarse manipulator and micro‐manipulator (Narishige, Tokyo, Japan) and an Axopatch 200 B amplifier (Axon Instruments, Foster City, CA) as previously described 16 . Voltage‐clamp protocol generation and data acquisition were managed by the A/D‐D/A interfaces (Digidata 1200; Axon Instruments) and Pclamp 6 software (Axon Instruments Foster City, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sphingosine, an important member of sphingolipids, is a ubiquitous component of the cell membrane and serves a pivotal role in cell growth, metabolism regulation, signal transduction, and various physiological function ( Gaggini et al, 2022 ; Grewe et al, 2022 ). Previous publications demonstrated that sphingosine and sphingosine-1-phosphate (its downstream product) were bioactive biomolecules which exerted proinflammatory effects and promoted proapoptotic properties in the vascular endothelial cell, contributing to the occurrence and development of cardiovascular diseases ( Bernacchioni et al, 2022 ; Kurano et al, 2022 ). In recent studies, sphingosine levels were proven to be shifted in the inner tissues and perilymph and aggravated the oxidative stress and inflammation in sensorineural hearing loss and ototoxicity ( Romero-Guevara et al, 2015 ; Cencetti et al, 2019 ; Wang et al, 2020 ; Ramkumar et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%